On frequency response based prediction of rotor-stator circular rub behaviour - M. Cole (2018)
This paper concerns model-based prediction of rub-induced backward whirl of rotors. A Nyquist-type frequency response analysis is introduced that gives useful insight into the influence of rotor-stator contact characteristics, in terms of compliance and friction, on the existence and stability of limit-cycle backward whirl solutions to the equations of motion. A number of test cases illustrate how the theory may be used to establish parametric boundaries for stability. It is found that the existence or non-existence of limit cycle whirl responses is highly sensitive to the type of compliant contact model used to represent the interaction of the rotor and its surround. The implications of these results for realistic system modelling, as well as the possibility of using the theory to compare or improve rotor designs, are discussed. © IMechE 2008.